Premiere Pro Guru: Audio Workflow and the Essential Sound Panel. - Winters, Luisa (linkedin.com, 2019)
Work effectively with the Essential Sound panel in Adobe Premiere Pro. Learn various methods for mixing audio, addressing problems, and enhancing tracks for a polished finish.